Gracious freedom as an effect of the grace of the sacraments of initiation in human life - Petrov, George Daniel; Zagan, Andrei-Dragoș; Fofiu, Gheorghe Adrian (Technium Social Sciences Journal, 2022)
In Orthodox theology, the sacraments of initiation through which a person becomes an Orthodox Christian, have, in addition to the classical effects already known, other effects such as haric freedom. Practically, in addition to the fact that the newly baptized person enters the Church of Christ, he also receives liberation from the slavery of sin in which the progenitors Adam and Eve once fell, and through them the whole of humanity. Even if freedom is a gift of man through creation, the choice of sin brought with it enslavement, thus the partial loss of the state of freedom. Therefore, in what follows we will exemplify the difference between natural and grace freedom.